Penerapan Media Gambar Beserta Permainan Untuk Mengurangi Buta Huruf Pada Panti Asuhan Kasihani Anak Indonesia - nanda hadiarty; Fajar Utama Ritonga (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The purpose of learning through picture media and game media is to reduce the number of illiterates in the Indonesian Children's Children's Orphanage. The implementation of this PKL activity starts from September 2021 until December 2021. The time for this activity is carried out for 4 months. The method used in this PKM training is Groupwork. The activity consists of 5 points in the Groupwork stage, namely the Assessment Stage, Planning Stage, Intervention Stage, Evaluation Stage and Termination Stage. The results achieved from the activities based on the 5 stages that have been carried out earlier, it can be seen that there has been a fairly rapid development of children in learning to memorize the alphabet. Efforts to establish a learning environment in accordance with the theory mentioned earlier, the formation of an interactive learning environment using images, videos and through games has succeeded in increasing interest, concentration and children's recognition of letters well.